High capacity reversible hydrogen storage in Si substituted and Li decorated C20 fullerene: Acumen from density functional theory simulations - Jaiswal, Ankita; Chakraborty, Brahmananda; Sahu, Sridhar (International journal of energy research, 2022)
Summary This article addresses the reversible hydrogen storage capacities of lithium (Li) decorated and silicon (Si) substituted C20 fullerene using density functional theory. The stabilities of the newly designed Si2C18Li6 and Si4C16Li6 cages have been verified from their chemical hardnesses and HOMO−LUMO gaps. The interaction between H2 molecules and the Li centers occurs via a Niu‐Rao‐Jena type interaction. Topological analysis reveals that the nature of the bonding between H2 and the host clusters as a weak non‐covalent type. The H2 molecules in Si2C18Li6‐nH2 and Si4C16Li6‐nH2 are found to be adsorbed in quasi‐molecular fashion with the average adsorption energies in the range of 0.119 eV ‐ 0.139 eV and 0.131 eV ‐ 0.140 eV, respectively. The molecular dynamics simulation confirms the thermal stability and structural integrity of Li decorated Si2C18 and Si4C16 cages at a relatively high temperature of 400 K. It has been observed that between 300 K and 400 K, most of the hydrogen molecules get desorbed from the host cages, and the structures of the clusters remain almost intact after the complete desorption, which confirmed their reversibility. The practical storage capacities of Si2C18Li6 and Si4C16Li6 cages at temperature and pressure ranges of 40 K ‐ 140 K, 40 K ‐ 120 K, and 1 ‐ 60 bar are found to be 16.09 % and 14.77 wt%, which are fairly high as compared to the target of the United States Department of Energy (5.5 wt% by 2020). Moreover, we have found that at the temperature and pressure of 200 K and 40 bar, the gravimetric density of both the cages are approximately 5.5 wt%. Hence, the newly designed Si2C18Li6 and Si4C16Li6 cages can be considered as promising materials for hydrogen storage systems. This article demonstrates that Si doped and Li functionalized C20 cages can hold H2 molecules with a maximum gravimetric density of 16.15% with adsorption energy lying in the range of 0.12 eV‐0.14 eV. Si doping enhances the H2 adsorption capacity of the carbon cages. The studied hydrogenated cages are found to reversible at nearby room temperature and pressure.